Financial Aid Nudges: A National Experiment With Informational Interventions. (June 2023) - Page, Lindsay C.; Sacerdote, Bruce I.; Goldrick-Rab, Sara; Castleman, Benjamin L.
Despite high prices, many college students do not re-file the Free Application for Federal Student Aid (FAFSA) or file late, making college less affordable. Low-cost technological interventions delivering personalized information and/or advising may improve refiling and academic outcomes, but questions remain regarding the efficacy of this approach at scale. This multi-pronged randomized experiment tested informational and framing text message interventions for a national sample of approximately 10, 000 undergraduates. The text outreach caused earlier FAFSA re-filing for some students. However, gains in re-filing during the active intervention period were not sustained after the intervention concluded and did not translate into additional federal financial aid or improved postsecondary persistence or attainment. Implications for the scaling and targeting of nudging are discussed.